Lignin-coated cellulose nanocrystal filled methacrylate composites prepared via 3D stereolithography printing: Mechanical reinforcement and thermal stabilization. (1st August 2017) - Feng, Xinhao; Yang, Zhaozhe; Chmely, Stephen; Wang, Qingwen; Wang, Siqun; Xie, Yanjun
Highlights: L-CNC reinforced methacrylate nanocomposites were produced by 3D-SL printing. A postcure was first used to improve the properties of printed nanocomposites. H-bonding between MA matrix and L-CNC was detected. Abstract: Various contents of lignin-coated cellulose nanocrystals (L-CNC) were incorporated into methacrylate (MA) resin and their mixture was used to prepare nanocomposites via 3D stereolithography (3D-SL) printing. Gaps were found between the L-CNC and MA matrix in 3D-SL printed nanocomposites before postcure. However, gaps decreased after postcure due to interactions between the L-CNC and MA molecules. Mechanical properties increased with the addition of 0.1% and 0.5% L-CNC after postcure, and the thermal stability was improved at 0.5% L-CNC. Dynamic mechanical analysis demonstrated that incorporation of L-CNC increased the storage modulus in the rubbery plateau. The loss factor had two transition regions, which gradually changed by merging together with increasing L-CNC content, and a broadening of the transition region was observed after postcure. In particular, the mechanical and thermal properties of 3D-SL printed nanocomposites, after postcure, exhibited higher improvement than those before postcure.